2021
DOI: 10.1007/s00330-021-08222-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of short-protocol emergency brain MRI after negative non-contrast CT for minor stroke detection

Abstract: Objectives To investigate the cost-effectiveness of supplemental short-protocol brain MRI after negative non-contrast CT for the detection of minor strokes in emergency patients with mild and unspecific neurological symptoms. Methods The economic evaluation was centered around a prospective single-center diagnostic accuracy study validating the use of short-protocol brain MRI in the emergency setting. A decision-analytic Markov model distinguished the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In this study, the 30 years costs of an MRI strategy for patients with normal CT were estimated to be $26 304 compared with costs of $27 109 with a CT-only strategy. 24 However, in a more extensive study, which modeled most of the care pathway, MRI was not cost-effective compared with any other imaging modality (with incremental costs of between £63 and £407). 19 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, the 30 years costs of an MRI strategy for patients with normal CT were estimated to be $26 304 compared with costs of $27 109 with a CT-only strategy. 24 However, in a more extensive study, which modeled most of the care pathway, MRI was not cost-effective compared with any other imaging modality (with incremental costs of between £63 and £407). 19 …”
Section: Discussionmentioning
confidence: 98%
“…In this study, the 30 years costs of an MRI strategy for patients with normal CT were estimated to be $26 304 compared with costs of $27 109 with a CT-only strategy. 24 However, in a more extensive study, which modeled most of the care pathway, MRI was not cost-effective compared with any other imaging modality (with incremental costs of between £63 and £407). 19 Countries or regions where access to MRI is not constrained could implement a policy of MRI scanning for all patients with transient or minor neurological symptoms and use the results of MRI to determine subsequent treatment.…”
Section: Sciencesmentioning
confidence: 98%
“…As a result, studies on the cost-effectiveness of brain MRI modality for patients with potential CSVD may be needed in the future. It has been reported that in patients with minor stroke, additional brain MRI scanning has been found to enable timely secondary prophylaxis, which results in lower costs and higher cumulative quality-adjusted life years 44 . In light of the heavy burden of CSVD-related functional disability and cognitive impairment, appropriate brain MRI scanning will most likely ensure early detection and timely interventions on CSVD, thereby reducing long-term expense and improving final outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ABCD3 serial score, Kiyohara et al discovered that adding intracranial arterial stenosis could further improve the score's predictive value for recurrent stroke (22). Although computed tomography and MRI are sensitive and accurate neuroimaging tools, they are often expensive and dependent on practitioners' interpretation skills, and their utilization rates vary widely (23,24). Carotid Doppler sonography provides a low-cost, lowrisk, and highly portable alternative modality for evaluating the vessels of patients with acute stroke (25).…”
Section: Introductionmentioning
confidence: 99%